Realisasi Diri Melalui Kontemplasi Menuju Śūnyātiśūnya Perspektif Vijñàna Bhairawa (Kajian Filosofi) - Prasanthy Devi Maheswari; Hari Harsananda (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This article aims to know about how humans find a way to achieve their true Self. People with all their limitations try to understand what the real goal of life is. The goal of human life is not only to seek the happiness they feel by obtaining everything they want in this world, but that is actually beyond the earthly happiness. The goal is to achieve moksha or unite the Self (Ātman) with the Creator or God (Brahman). Another term also mentioned is that Ātman achieved liberation or release; The Ātman is free from all worldly attachment and escapes from the cycle of rebirth (punarbhawa). The efforts to achieve this ultimate goal are made by raising self-awareness towards godliness awareness which in this article is termed by achieving self-realization. This article uses the approach of literature studies with the philosophical methods, which is the interpretation about concept of self-realization by contemplating towards absolute voidness with the perspective of the holy scripture Vijñàna Bhairawa.